2020
DOI: 10.3390/coatings10090811
|View full text |Cite
|
Sign up to set email alerts
|

New 8-Hydroxyquinoline-Bearing Quinoxaline Derivatives as Effective Corrosion Inhibitors for Mild Steel in HCl: Electrochemical and Computational Investigations

Abstract: There has been substantial research undertaken on the role of green synthesized corrosion inhibitors as a substantial approach to inhibit the corrosion of metals and their alloys in acidic environments. Herein, electrochemical studies, surface characterization, and theoretical modeling were adopted to investigate the corrosion inhibition proprieties of novel synthesized quinoxaline derivatives bearing 8-Hydroxyquinoline, namely 1-((8-hydroxyquinolin-5-yl) methyl)-3,6-dimethylquinoxalin-2(1H)-one (Q1) and 1-((8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 57 publications
3
7
0
Order By: Relevance
“…The quinoxalinedione derivatives have attracted attention in several molecular applications [1][2][3][4]. Synthesis, energetic and structural properties of some quinoxalinedione derivatives were made by our group [5][6][7][8][9][10]. Spectroscopic data are in agreement with literature [5,8,10].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The quinoxalinedione derivatives have attracted attention in several molecular applications [1][2][3][4]. Synthesis, energetic and structural properties of some quinoxalinedione derivatives were made by our group [5][6][7][8][9][10]. Spectroscopic data are in agreement with literature [5,8,10].…”
Section: Introductionsupporting
confidence: 65%
“…Synthesis, energetic and structural properties of some quinoxalinedione derivatives were made by our group [5][6][7][8][9][10]. Spectroscopic data are in agreement with literature [5,8,10]. Organic photovoltaic solar cells (OPVSC) pose an important potential for progress in the work for electricity production from low-cost compounds.…”
Section: Introductionsupporting
confidence: 58%
“…Figure 7 shows the RDF analysis results stemming from the consequence of the MD simulation data of two quinoxaline derivative inhibitor molecules (Q1 and Q2) cited in the literature [ 134 ]. These results are shown in the form of a plot of the distance r versus the probability g(r).…”
Section: Experimental and Theoretical Research Methods And Characteri...mentioning
confidence: 99%
“…Contrarily, Zhu et al [59] demonstrated the use of Fe(100) surface as the adsorption site for 2-aminobenzimidazole derivative inhibitor. The order of surface energy of the iron surface is Fe(110) < Fe(100) < Fe (111), which makes Fe (110) to be the most stable, followed by Fe(100) and Fe (111) facets [60]. Regardless of the type of ferrous metal (carbon steel, alloy steel or stainless steel) studied experimentally, pure iron atoms instead of a mixture of iron with alloying elements are usually used for theoretical studies [11,38,[61][62][63].…”
Section: Construction Of a Corrosion Systemmentioning
confidence: 99%